Study on the Three-Dimensional Evolution of Ionospheric Disturbances in China During the Geomagnetic Storm on December 1, 2023 - Yifei Yang; Jian Kong; Xiangping Chen; Congcong Ling; Changzeng Tang; Yibin Yao; Zhaorong Zhu (Atmosphere)
On 1 December 2023, a strong geomagnetic storm was triggered by an interplanetary shock caused by a coronal mass ejection (CME). This study used data from 193 Global Navigation Satellite System (GNSS) observation stations in China to study the three-dimensional morphological total electron content (TEC) disturbances during this storm. By analyzing GNSS TEC data from 15 GNSS stations along the magnetic field lines, it was found that TEC disturbances spread from low to high latitudes, confirmed by ionosonde NmF2 data. The TEC disturbance first appeared at the LJHP station, (21.68° N) at 11:30 UT and propagated to the BJFS station (39.60° N) at 13:30 UT with a propagation speed of about 217 m/s and maximum amplitude of ±0.2 m. The TEC disturbance lasted the longest, approximately 4 h, between latitudes 25° N and 32° N. Additionally, this study investigated the ionosphere’s three-dimensional electron density distribution in the Guangxi region using an ionospheric tomography algorithm. Results showed that the TEC disturbances were mainly concentrated between 450 and 580 km in altitude. At 12:00 UT, the maximum change in electron density occurred at a 580 km height at 26° N, 112° E, increasing by 20.54 total electron content unit (TECU). During the main phase of the geomagnetic storm, the electron density expanded from higher to lower layers, while during the recovery phase, it recovered from the lower layers to the higher layers.